Modulation of the N-methyl-D-aspartate channel by extracellular H+. - Tang, C M (1990)
The influence of external [H+] on whole-cell and single-channel currents activated by glutamate agonists was studied in rat hippocampal neurons. In the pH range between 6.6 and 8.0, changes in external [H+] had negligible influence on the amplitude and kinetics of the monovalent ion-carrying currents activated by the agonists quisqualate and kainate. The divalent ion-carrying N-methyl-D-aspartate (NMDA)-activated current, on the other hand, was strongly modulated by extracellular [H+]. Increased external [H+] suppressed, whereas decreased external [H+] enhanced, the NMDA-activated current. Changes in internal [H+] had little or no effect on the NMDA-activated current. Modulation of the NMDA-activated current resulted primarily from changes in the number of channel openings. Neither the unitary conductance nor the individual open dwell-times were significantly affected. These results suggest that the protonation site is on the external aspect of the channel and is far removed from the channel permeation pathway. Because interactions between H+, NMDA, and glycine in activating the current were predominantly noncompetitive, our results suggest that the modulatory effect of H+ was not associated with changes in receptor-agonist affinities. These results suggest that modulation of the NMDA-receptor channel by [H+] may be an intrinsic protective mechanism by which calcium influx into neurons is regulated, particularly in hypoxic/ischemic conditions.